EPEN-16. Epithelial Progenitor Cell Abundance and Copy Number Variant Gains and Losses Impact the Biology of Recurrent Ependymoma. (3rd June 2022) - Norris, Gregory; Fu, Rui; Riemondy, Kent; Willard, Nicholas; Griesinger, Andrea; Amani, Vladamir; Grimaldi, Enrique; Harris, Faith; Gilani, Ahmed; Hankinson, Todd; Hesselberth, Jay; Foreman, Nicholas; et al.
Abstract: Ependymoma (EPN) is a common pediatric brain tumor that is fatal in approximately 50% of cases. Posterior fossa A (PFA) EPN has the highest rate of recurrence and the worst prognosis of all EPN subtypes. At relapse, it is typically incurable even with re-resection and re-irradiation. The biology of recurrent ependymoma remains largely unknown, which hinders clinical advances. In this study, we use paired samples of primary and recurrent disease from the same patient to investigate the drivers of recurrence. DNA methylation studies reveal frequent copy number variants at recurrence that were not present at primary presentation. We report a frequent gain of chromosome 1q and loss of 6p at recurrence, which has not been previously reported and may be a driver of recurrent disease. We have previously shown that PFA EPN is comprised of 4 main neoplastic cell populations, two well-differentiated populations termed ciliated and transportive ependymal cells, a mesenchymal cell population, and an undifferentiated population. Using spatial transcriptomics (Visium) integrated with single-nuclei RNA-seq (Chromium), we discovered that a highly proliferative EPN progenitor population of epithelial lineage is significantly upregulated at recurrence which we hypothesize drives refractory disease. Accordingly, we found higher expression of EPN progenitor gene signatures in bulk RNA transcriptomes of primary tumors that later recurred compared to tumors that never recurred. Together, these findings highlight the biologic differences between primary and recurrent disease and add to our understanding of treatment resistance in childhood ependymoma.